Evaluation of the combination of oxaliplatin and 5-fluorouracil or gemcitabine in patients with sporadic metastatic pulmonary carcinoid tumors. (June 2016) - Walter, T.; Planchard, D.; Bouledrak, K.; Scoazec, J.Y.; Souquet, P.J.; Dussol, A.S.; Guigay, J.; Hervieu, V.; Berdelou, A.; Ducreux, M.; Arpin, D.; Lombard-Bohas, C.; et al.
Highlights: Treatments in lung metastatic carcinoid are derived from digestive neuroendocrine tumors (NETs). Cytotoxic chemotherapy is one of this treatment, but needs to be validated in lung NETs. Among them, alkylating agents are mainly used, but new agents like oxaliplatin seem promising. We here report the efficacy of oxaliplatin-based chemotherapy in lung carcinoid tumors. Abstract: Objectives: The aim of this retrospective study was to analyse the efficacy of gemcitabine-oxaliplatin (gemox) or 5-fluorouracil-oxaliplatin (folfox) in the treatment of metastatic pulmonary carcinoid tumors. Patients and methods: 45 patients were included in two tertiary referral centers between January 1999 and January 2013. Typical, atypical carcinoids or not otherwise specified carcinoids were diagnosed according to WHO criteria in 19%, 57%, and 24% of cases by two expert pathologists. Patients had synchronous (38%) or metachronous (62%) metastastic disease (median of 2 (1–5) metastatic sites). Seventy-nine percent had progressive disease before start of chemotherapy. Treatment consisted of: gemcitabine 1000 mg/m 2 and oxaliplatin 100 mg/m 2 every 2 weeks (gemox regimen, n = 24) or 5-fluorouracil (5-FU) (400 mg/m 2 in bolus injection and 5-FU 2400 mg/m 2 in 46 h-infusion) and oxaliplatin 85 mg/m 2 (folfox regimen, n = 21) every 2 weeks. Tumor response was assessed according to RECIST criteria every 8–12 weeks. Progression free survival and overall survival were assessed using Kaplan Meier curves. Results: Patients received oxaliplatin-based chemotherapy in first-line (20%), second-line (33%), or post-second-line (47%) systemic treatment. The median number of cycles was 8 (1–12). Nine (20%) stopped oxaliplatin before 8 cycles because of toxicity. Nine patients (20%) had a partial response and 29 (64%) had stable disease. Median progression free survival (PFS) was 15 (6–25) months. Median overall survival (OS) was 34 (21–49) months. No significant difference was observed in response and PFS between either regimens. Conclusions: Our results suggest that either gemcitabine-oxaliplatin or 5-fluorouracil-oxaliplatin combinations are attractive chemotherapy regimen in metastatic pulmonary carcinoid tumors.